Contemporary Progression, Agile Applications and Impending Scope of Internet of Things - Praveena, TS; Naga Jyothi, M; Surya Prakash, M (International Journal of Computer Sciences and Engineering, 2025)
Internet of Things (IoT) can be defined as a network of physical objects, devices that contain embedded technology (like intelligent sensors, controllers etc.) which can communicate, sense, or interact with internal and external systems. In other words, when objects can sense and communicate, it changes how and where decisions are made, and who makes them and accordingly operations can be carried out. A latest and very fast emerging shift in networking and communications is the Internet of Things. This technology provides an easier way of communication of devices with the minimal interaction of human. IoT takes a leap because of advancement in network interconnections and computing ability to propose fresh techniques. With computation, connectivity, and data storage becoming more advanced there has been an expansion of IoT based application solutions in diversified domains right from health care to public safety, agriculture, from assembly line scheduling to manufacturing and various other technological domains. Different IoT based applications have been explored and possible approach for enhancing the use of this technology have been depicted in this paper. Future directions and suggestions for effectively and efficiently improving the IoT based application areas have been shown. This paper will provide a better insight to carry out research in the field of IoT.